2009
DOI: 10.4103/1319-3767.54746
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of the clinical profile and prognostic indicators in patients of alcoholic liver disease admitted to a tertiary care teaching hospital in Western Nepal

Abstract: Background/Aim:Alcohol is the most common substance abused in Nepal. Liver disease caused by alcohol abuse, including its end stage, cirrhosis, is a major health care problem, which is difficult to treat.Objectives:To study the demographic profile, laboratory parameters, complications and their prognostic implications among patients of alcoholic liver disease (ALD).Materials and Methods:Records of all patients of ALD admitted from January 1' 2005 to December 31' 2006 were studied and followed up to December 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

25
23
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 10 publications
(14 reference statements)
25
23
3
Order By: Relevance
“…Features of hepatic encephalopathy were seen in 16% of the cases. In previous studies also ascites was common finding Suthar et al (60%), 16 Pathak et al (57.5%), 18 Mendenhall (50.9%). 19 Hepatomegaly which was confirmed by abdominal ultrasonography was seen in 20 (33%) case and splenomegaly in 25 (41%), while in study by Suthar et al 11 hepatomegaly and splenomegaly was seen in 50% and 60% cases respectively.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Features of hepatic encephalopathy were seen in 16% of the cases. In previous studies also ascites was common finding Suthar et al (60%), 16 Pathak et al (57.5%), 18 Mendenhall (50.9%). 19 Hepatomegaly which was confirmed by abdominal ultrasonography was seen in 20 (33%) case and splenomegaly in 25 (41%), while in study by Suthar et al 11 hepatomegaly and splenomegaly was seen in 50% and 60% cases respectively.…”
Section: Discussionmentioning
confidence: 77%
“…The mean total leucocyte count was 8056/mm 3 . Thrombocytopenia was seen in 73 % of cases with minimum platelet count of 27000/mm 3 while in study by Pathak et al 18 it was seen in 57.9% cases. INR was deranged in 38% of cases which was in keeping with other studies on alcoholic liver disease.…”
mentioning
confidence: 82%
“…19 Numerous studies have shown that ascites is associated with an increased mortality rate in patients with cirrhosis. 20,21 To understand the connection between MELDNa as a mortality predictor in patients with AH and ascites, we need to consider the physiology behind hyponatremia in these patients. The development of hyponatremia in cirrhotic patients has been linked to activation of the vasopressin system.…”
Section: Discussionmentioning
confidence: 99%
“…Shahid Aziz et al, ascites was seen in 53.8% and upper GI bleed in 25.1% patients. [17] While hepatitis B infection is more prevalent in the Asian and Sub-Saharan Africa in our study cirrhosis was mostly alcohol related (70%). Alcohol was the commonest aetiology in a study by R Maskey et al [19] However, in a study from Pakistan, the common aetiologies were due to HCV (67.7%) and HBV (18%).…”
Section: Discussionmentioning
confidence: 50%
“…et al, where 80.7% among 181 patients were males. [17] Higher incidence was also reported by Paul SB et al with a M:F ratio of 6.1:1 among cirrhotics. [18] This difference is due to high incidence of ethanol intake among men compared to women, which is the major aetiology of chronic liver disease and also due to differences in the medical care seeking practice among both sexes.…”
Section: Discussionmentioning
confidence: 71%